Sistem Pemesanan Berbasis Laravel Livewire dengan WhatsApp Gateway di Perumahan Bumi Coprayan Indah Pekalongan - Yoga Bagas Kurniawan; Tresi Aprilia; Muhammad Khozin; M. Achsin Samas (Jurnal Teknologi Terpadu, 2026)
The housing unit reservation system is still manual, with prospective buyers making reservations directly at the location offline, which often causes inefficiency, recording errors, and delays in information to prospective buyers. Therefore, this study aims to develop a Laravel and Livewire-based Housing Reservation Management System with a WhatsApp Gateway for Bumi Coprayan Indah Housing. This system is designed to enable prospective buyers to make housing unit reservations online, manage reservation data more efficiently, and receive automatic notifications via WhatsApp. The research method used is the Waterfall-based software development method, with the Laravel 10 framework, and the stages are requirements analysis, system design, implementation, and testing using the Black-Box Testing method and User Acceptance Testing (UAT). The test results indicate that the developed system functions well according to the predefined specifications. Based on these results, user satisfaction ranges from 76% to 80.4%, with the highest score for the house search feature (80.4%) and the lowest for the efficiency of the booking process (76%). This indicates that the system has been well accepted by users. The implementation of this system has a positive impact on reservation efficiency, reduces recording errors, and facilitates communication between property developers and prospective buyers. This system is expected to be an innovative solution for digitizing the housing reservation process in a more modern and structured manner.